The spatio-temporal evolution of multiple myeloma from baseline to relapse-refractory states - Rasche, Leo; Schinke, Carolina; Maura, Francesco; Bauer, Michael A.; Ashby, Cody; Deshpande, Shayu; Poos, Alexandra; Zangari, Maurizio; Thanendrarajan, Sharmilan; Davies, Faith E.; Walker, Brian A.; Barlogie, Bart; et al. (Nature Communications, 2022)
Deciphering Multiple Myeloma evolution in the whole bone marrow is key to inform curative strategies. Here, we perform spatial-longitudinal whole-exome sequencing, including 140 samples collected from 24 Multiple Myeloma patients during up to 14 years. Applying imaging-guided sampling we observe three evolutionary patterns, including relapse driven by a single-cell expansion, competing/co-existing sub-clones, and unique sub-clones at distinct locations. While we do not find the unique relapse sub-clone in the baseline focal lesion(s), we show a close phylogenetic relationship between baseline focal lesions and relapse disease, highlighting focal lesions as hotspots of tumor evolution. In patients with ≥3 focal lesions on positron-emission-tomography at diagnosis, relapse is driven by multiple distinct sub-clones, whereas in other patients, a single-cell expansion is typically seen (p < 0.01). Notably, we observe resistant sub-clones that can be hidden over years, suggesting that a prerequisite for curative therapies would be to overcome not only tumor heterogeneity but also dormancy.
Gesehen am 01.09.2022